2019
DOI: 10.1002/tox.22878
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 mediated Smad signaling pathway and EMT in hepatic fibrosis induced by Nano NiO in vivo and in vitro

Abstract: Nickel oxide nanoparticles (Nano NiO) bears hepatotoxicity, while whether it leads to liver fibrosis remains unclear. The aim of this study was to establish the Nano NiO‐induced hepatic fibrosis model in vivo and investigate the roles of transforming growth factor β1 (TGF‐β1) in Smad pathway activation, epithelial‐mesenchymal transition (EMT) occurrence, and extracellular matrix (ECM) deposition in vitro. Male Wistar rats were exposed to 0.015, 0.06, and 0.24 mg/kg Nano NiO by intratracheal instilling twice a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 71 publications
2
35
0
Order By: Relevance
“…These data are similar to a recent report, suggesting that HGF and/or emodin exhibit antifibrotic effects via suppression of the EMT process. TGFβ 1 signaling has been confirmed to be involved in fibrosis, 37,38 and is activated persistently in fibrosis. 39,40 Smad4 is at the core of the TGFβ 1 -signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These data are similar to a recent report, suggesting that HGF and/or emodin exhibit antifibrotic effects via suppression of the EMT process. TGFβ 1 signaling has been confirmed to be involved in fibrosis, 37,38 and is activated persistently in fibrosis. 39,40 Smad4 is at the core of the TGFβ 1 -signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[47] Nickel nanoparticles (44 nm) instilled intratracheally in Wistar rats led to increased staining for collagen-I in treated rats, showing that long-term exposure to nickel NPs was induced fibrosis. [48] Chen et al also found that mice injected intraperitoneally with titanium dioxide NPs (100 nm) developed hepatic fibrosis around the central vein, corresponding with areas of titanium dioxide NP attachment. [49] Exposure to silicon dioxide NPs (70 nm) twice a week for four weeks induced higher levels of the liver fibrosis marker hydroxyproline accompanying an increase in hepatic collagen staining in mice.…”
Section: Metallic Nps Can Modulate Liver Fibrosis Through Modifying Hmentioning
confidence: 98%
“…We note however that NPs can damage DNA, as well as provoke or worsen liver disorders such as liver fibrosis and steatosis. [48,49,109,113,114,121] Given that HCC is the terminal state for many liver disorders, [122] sufficiently long exposure periods coupled with a high dosage can presumably promote HCC development. As most NP hepatotoxicity studies rarely last longer than one year (Table 2), it may be that our current experimental models of exposing rodents to NPs are simply not being performed long enough for HCC to develop.…”
Section: Metallic Nps and Hepatocellular Cancermentioning
confidence: 99%
“…Data in the work [39] indicate that NiO NPs may produce fibrogenic effects on liver cells; it was shown that HEPG2 cells exposure to these NPs in a concentration equal to 100 µg/ml resulted in elevated expression of TGF-β1, p-Smad2, p-Smad3, -actin-smooth muscles, matrix metalloproteinase (MMP) of isoform 9, tissue inhibitor of metalloproteinase (TIMP)-1 and reduced E-cadherin and Smad7.…”
Section: Cytotoxicity Of Ni-containing Nanomaterialsmentioning
confidence: 99%